Vital personality scores and healthy aging: Life-course associations and familial transmission. (September 2021) - Wertz, Jasmin; Israel, Salomon; Arseneault, Louise; Belsky, Daniel W.; Bourassa, Kyle J.; Harrington, HonaLee; Houts, Renate; Poulton, Richie; Richmond-Rakerd, Leah S.; Røysamb, Espen; Moffitt, Terrie E.; Caspi, Avshalom
Abstract: Objectives: Personality traits are linked with healthy aging, but it is not clear how these associations come to manifest across the life-course and across generations. To study this question, we tested a series of hypotheses about (a) personality-trait prediction of markers of healthy aging across the life-course, (b) developmental origins, stability and change of links between personality and healthy aging across time, and (c) intergenerational transmission of links between personality and healthy aging. For our analyses we used a measure that aggregates the contributions of Big 5 personality traits to healthy aging: a "vital personality" score. Methods: Data came from two population-based longitudinal cohort studies, one based in New Zealand and the other in the UK, comprising over 6000 study members across two generations, and spanning an age range from birth to late life. Results: Our analyses revealed three main findings: first, individuals with higher vital personality scores engaged in fewer health-risk behaviors, aged slower, and lived longer. Second, individuals' vital personality scores were preceded by differences in early-life temperament and were relatively stable across adulthood, but also increased from young adulthood to midlife. Third, individuals with higher vital personality scores had children with similarly vital partners, promoted healthier behaviors in their children, and had children who grew up to have more vital personality scores themselves, for genetic and environmental reasons. Conclusion: Our study shows how the health benefits associated with personality accrue throughout the life-course and across generations. Highlights: A multi-trait index of 'vital personality' was derived. Individuals with higher vital personality scores aged more slowly. Individuals with higher vital personality scores had healthier lifestyles. Parents with higher vital personality scores promoted healthier habits in their children. Findings replicated in two cohorts.